Radiography, abdominal CT and MRI compared with sacroiliac joint CT in diagnosis of structural sacroiliitis. Issue 95 (October 2017) - Melchior, Julian; Azraq, Yusef; Chary-Valckenaere, Isabelle; Rat, Anne-Christine; Reignac, Marion; Texeira, Pedro; Blum, Alain; Loeuille, Damien
Abstract: Objective: To assess the performance of pelvic plain radiograph (radiography), abdominal CT and sacroiliac joint MRI (MRI) compared with sacroiliac joints CT (SI joint CT) for the diagnosis of structural sacroiliitis in a population suffering from spondyloarthritis (SpA) meeting the New York or ASAS criteria. Methods: All SpA patients eligible for biologic treatment who received a pre-therapeutic check-up including the four imaging techniques in the same year were selected from 2005 to 2012. An assessment of sacroiliitis was based independently by a rheumatologist and a radiologist on radiography according to the modified New York criteria and on abdominal CT, MRI and SI Joint CT depending on the presence of erosion on at least two consecutive slices. A final diagnosis was established for conflicting exams. Results: Of the 58 selected patients, sacroiliitis was diagnosed on radiography, abdominal CT, MRI and SI Joint CT in 32, 26, 34 and 35 patients, respectively. Inter-reader agreements for the grade of sacroiliitis were substantial with a weighted Kappa that varied between 0.60 and 0.76 and they were moderate for the diagnosis of sacroiliitis with a Kappa that varied between 0.45 and 0.55 for the four imaging modalities. The sensitivities of radiography, abdominal CT and MRI were 82.8%, 71.4% and 85.7% respectively and the specificities were 86.9%, 100% and 82.6% respectively with excellent accuracy and positive predictive value and good negative predictive value. Conclusion: This study demonstrates the relevance of MRI and abdominal CT for the diagnosis of structural sacroiliitis with good sensitivities and excellent specificities. These imaging modalities may also contribute for the diagnosis of structural sacroiliitis.